2012
DOI: 10.1002/aenm.201100773
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Inverted Tandem Polymer Solar Cells with a Solution‐Processed Recombination Layer

Abstract: Solution‐processed tandem polymer solar cells with an inverted polarity configuration provide a power conversion efficiency of 5.8%. The tandem cells use an almost loss‐free recombination layer and two photoactive layers, with wide and small bandgaps, to increase the power conversion efficiency beyond that of the corresponding single‐layer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 27 publications
3
82
0
Order By: Relevance
“…15,16 In addition, the inverted structure also matches well with the vertical phase separation of the active bulk heterojunction layer and thus enhances charge collection at the organic/electrode interfaces. 17,18 Solution processed ZnO nanoparticle (ZnONP) layers are widely used as cathodes for the inverted polymer solar cells 19,20 and n-type side of the recombination layer in tandem architectures 21,22 due to comparatively high electron conductivity, low work function, transparency and environmental stability. The use of ZnO layers is not without problems, however.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 In addition, the inverted structure also matches well with the vertical phase separation of the active bulk heterojunction layer and thus enhances charge collection at the organic/electrode interfaces. 17,18 Solution processed ZnO nanoparticle (ZnONP) layers are widely used as cathodes for the inverted polymer solar cells 19,20 and n-type side of the recombination layer in tandem architectures 21,22 due to comparatively high electron conductivity, low work function, transparency and environmental stability. The use of ZnO layers is not without problems, however.…”
Section: Introductionmentioning
confidence: 99%
“…Kouijzer et al [ 36 ] analyzed blends of a small band gap ( E g = 1.46 eV) diketopyrrolopyrrole-quinquethiophene alternating copolymer (PDPP5T) [ 37,38 ] with [6,6]-phenyl-C71-butyric acid methyl ester ([70]PCBM), and suggested that the phase separation in PDPP5T:[70]PCBM blends is due to spinodal liquidliquid (L-L) demixing. In a previous paper, [ 39 ] we have shown how it is possible to use a one-dimensional (1D) drift-diffusion model [ 40 ] to simulate the current-voltage ( J-V ) characteristics of such PDPP5T:[70]PCBM blends, either homogeneous or phase separated.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Currently, combinations of p-type metallic poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) and n-type semiconducting metal oxides (e.g., zinc oxide (ZnO) or titanium sub-oxide (TiO x )) are widely used in RLs due to their appropriate mechanical, optical, and electrical properties. [7][8][9] However, a signifi cant mismatch between the Fermi levels (i.e., WFs) of PEDOT:PSS and metal oxides results in the charge carrier exchange between two materials for aligning their Fermi levels, thus forming depletion-induced Schottky barrier at the RL interface. Furthermore, sol-gel-processed metal oxides possess many charge trap sites.…”
mentioning
confidence: 99%
“…These device geometries include tandem architectures [6][7][8][9] and inverted structures. [7][8][9] Tandem PSCs are composed of two serially connected sub-cells that use low-and high-bandgap conjugated polymers with complementary absorption spectra to harvest the full solar spectrum. In contrast, inverted PSCs allow for the use of air-stable, printable metal electrodes (e.g., Ag ink) and thus exhibit much better device stability and printability than conventional PSCs that use low-work-function (WF) metal electrodes.…”
mentioning
confidence: 99%